2023
DOI: 10.1186/s10020-023-00737-z
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and hearing loss

Yuxin Deng,
Sen Chen,
Jun Hu

Abstract: Diabetes mellitus (DM) is a major disease threatening human health and its incidence is increasing year on year. As a chronic complication of DM, hearing loss mostly occurs undetectably. However, the mechanism of this diabetes-related hearing loss (DRHL) remains unclear and there is no effective clinical treatment. Studies of animal or human pathology show that DM causes damage to the blood vessels, spiral ganglion neurons, afferent nerve fibers, the organ of Corti, and the stria vascularis of the inner ear. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Previous studies have identified DM as a potential risk factor for HL ( 21 , 22 ). However, there are different types of HL, which are often classified by anatomical deficit as conductive, sensorineural, or mixed ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified DM as a potential risk factor for HL ( 21 , 22 ). However, there are different types of HL, which are often classified by anatomical deficit as conductive, sensorineural, or mixed ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have highlighted a greater incidence of HL in DM patients compared to nondiabetic patients, and revealed a direct correlation between the severity of DM and the extent of HL ( 21 23 ). Patients with T2DM have shown both HL and vestibular dysfunction ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals having Type 2 diabetes are at increased risk of auditory complications, including sensory neuropathy, cellular damage, accelerated atherosclerosis, and vasculitis [10]. DM is known to affect cochlear cells, spiral ganglion neurons, the organ of Corti, and the stria vascularis thereby affecting auditory acuity in individuals with DM [11]. In addition to hearing loss, these changes also have repercussions that could account for symptoms such as dizziness and tinnitus [12].Despite knowing that DM affects hearing this aspect of management largely remains neglected and all the efforts are directed toward managing diabetes and its other complications [13].…”
Section: Introductionmentioning
confidence: 99%